Free vibration of an axially functionally graded pile with pinned ends embedded in Winkler-Pasternak elastic medium - Cetin, Dogan; Simsek, Mesut (TECHNO-PRESS, 2011)
In the present study, free vibration of an axially functionally graded (AFG) pile embedded in Winkler-Pasternak elastic foundation is analyzed within the framework of the Euler-Bernoulli beam theory. The material properties of the pile vary continuously in the axial direction according to the power-law form. The frequency equation is obtained by using Lagrange's equations. The unknown functions denoting the transverse deflections of the AFG pile is expressed in modal form. In this study, the effects of material variations, the parameters of the elastic foundation on the fundamental frequencies are examined. It is believed that the tabulated results will be a reference with which other researchers can compare their results.
Keywords: vibration; pile; functionally graded material; Winkler-Pasternak foundation; SEMI-INVERSE METHOD; TIMOSHENKO BEAM; FORCED VIBRATION; COLUMNS; Engineering